(untitled) (Genitri: Jurnal Pengabdian Masyarakat Bidang Kesehatan, 2024)
According to the research conducted by Yuniati and Dewi (2023), the implementation of hypnoprenatal and prenatal yoga among pregnant women in the Province of Bali remains notably low. One contributing factor to this low uptake is the insufficient number of Independent Midwife Practice Places (TPMB) or midwives who are capable of administering hypnotherapy care to pregnant women. This community service program aims to provide education and information to posyandu cadres regarding the data on hypnoprenatal application and its benefits for pregnant women. Through this initiative, it is hoped that the cadres can increase their awareness and knowledge about the importance of hypnoprenatal for expectant mothers. The educational activities proceeded smoothly and were well-received by the cadres. The posyandu cadres exhibited great enthusiasm in learning about and disseminating information related to hypnoprenatal to pregnant women within their communities, particularly in Banjar Kaja, Desa Serangan, Denpasar. With this education, it is hoped that more pregnant women will understand the benefits of hypnoprenatal and prenatal yoga, thereby increasing their interest and application of these methods among pregnant women, both specifically in Desa Serangan and more generally across the Province of Bali. Through the active support and participation of the cadres, it is anticipated that the practices of hypnoprenatal and prenatal yoga will become more widely known and accepted by the community, especially among pregnant women. This, in turn, will enable them to experience the benefits of these methods in preparing for a more comfortable and less anxiety-ridden childbirth.